Monosynaptic Tracing Success Depends Critically on Helper Virus Concentrations - Lavin, Thomas K.; Jin, Lei; Lea, Nicholas E.; Wickersham, Ian R. (Frontiers in Synaptic Neuroscience, 2020)
Monosynaptically-restricted transsynaptic tracing using deletion-mutant rabies virus has become a widely used technique in neuroscience, allowing identification, imaging, and manipulation of neurons directly presynaptic to a starting neuronal population. Its most common implementation is to use Cre mouse lines in combination with Cre-dependent "helper" adeno-associated viral vectors (AAVs) to supply the required genes to the targeted population before subsequent injection of a first-generation (∆G) rabies viral vector. Here we show that the efficiency of transsynaptic spread and the degree of nonspecific labeling in wild-type control animals depend strongly on the concentrations of these helper AAVs. Our results suggest practical guidelines for achieving good results.